Pattern of Children's Education In Surah Luqman (Quran 31:13-19) Through The Lens of Islamic Education Philosophy - Nasikhin; Ratna muthia; Maulana Diaz (Reforma: Jurnal Pendidikan dan Pembelajaran, 2025)
Education is the basis for acquiring knowledge, including religious and moral values. The knowledge that humans get from education starts from humans in the womb with the first educator being their parents. To educate children, both parents have a strategy called an educational pattern. Education patterns are very diverse, especially education and childcare patterns. In Islam, there are many figures who can be examples in educating children, one of which is Luqman. Luqman became a role model for parents in educating their children, even Luqman's example in educating his children contained in the Qur'an Surah Luqman. In Surah Luqman verses 13-19 describe the pattern of education to children by giving advice, exemplifying commendable behavior and upholding the teachings of Islam in life. The verse emphasizes a balanced approach to education that ensures that children's lives remain in harmony with Islamic teachings and values. The study of educational patterns based on surah Al-Qur'an Luqman verses 13-19 can be a reference for parents in providing education to children in accordance with the Qur'an, so as to form children's character with good knowledge, morals and beliefs.